2019
DOI: 10.1002/1878-0261.12427
|View full text |Cite
|
Sign up to set email alerts
|

Six‐gene Assay as a new biomarker in the blood of patients with colorectal cancer: establishment and clinical validation

Abstract: Colorectal cancer ( CRC ) is the second most common cancer in men and the third most common cancer in women. Although long‐term survival has improved over the past 30 years, at least 50% of patients with CRC will develop metastases after diagnosis. In this study, we examined whether quantifying the mRNA of six CRC ‐related genes in the blood could improve disease assessment through detection of circulating tumor cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Because Kelch-like ECH-associated protein 1 (Keap1)/Nrf2 signaling is a key mediator in thyroid pathophysiology and thyroid cancer, the regulation of AOX1 by the Keap/Nrf2 pathway might account for part of the pathogenesis of PTC (38). Both gene expression in tissues and protein contents in plasma have promising diagnostic and prognostic potential in many tumors (39)(40)(41). A previously study reported that serum TPO was not a useful marker for patients with differentiated thyroid carcinoma (42).…”
Section: Discussionmentioning
confidence: 99%
“…Because Kelch-like ECH-associated protein 1 (Keap1)/Nrf2 signaling is a key mediator in thyroid pathophysiology and thyroid cancer, the regulation of AOX1 by the Keap/Nrf2 pathway might account for part of the pathogenesis of PTC (38). Both gene expression in tissues and protein contents in plasma have promising diagnostic and prognostic potential in many tumors (39)(40)(41). A previously study reported that serum TPO was not a useful marker for patients with differentiated thyroid carcinoma (42).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression has promising diagnostic potential in a number of types of cancer, including colorectal, ovarian, and breast cancer (4345). In the present study, the calculated AUC values ranged from 0.7–0.9, which is considered an excellent discriminatory power (46), while the AUC values for CDH6, COL13A1, ADH1B and TBC1D4 were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC), as the most popular cancer around the world, is seriously endangering the health of all humankind. Its incidence rate ranks second in men and third in women [ 1 ]. According to cancer statistics in the United States, about 147,950 people were diagnosed with CRC and nearly 53,200 people died of CRC in 2020 [ 2 ].…”
Section: Highlightsmentioning
confidence: 99%